A review on seawater as concrete composites and its effects on the strength and durability - Hussain, Zahid; Md Noor, Nurazuwa (Penerbit UTHM, 2020)
The world is facing a big challenge of balancing a growing population and demand with a natural environment that is increasingly under stress. The rapidly changing environmental conditions especially intensity and frequency of extreme weather it has now become very important to explore in green technology. Effective use of natural resources is pressing concern. Particularly, water resources for drinking are predicted to be in serious shortage in 2050 due to increase in population and rapid urbanization throughout the world. The beginning of the 21st century is straddled with enormous environmental problems of which water shortage is one of the most serious. It is a well-known fact that fresh water resources are continuously declining throughout the world and according to a report by the United Nations, water will be very short in future. It is expected that 5bn people will be short of drinking water in 2050 [1]. In another report published by OECD, it is stated that a number of people living in river basins will be under severe water stress which is expected to be double in 2050 ..